2009
DOI: 10.1088/0957-0233/20/7/075502
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz pulse imaging for tree-ring analysis: a preliminary study for dendrochronology applications

Abstract: Time-domain terahertz reflection imaging is presented as a novel method of measuring otherwise inaccessible tree rings in wooden cultural heritage for the purpose of tree-ring crossdating. Axial and lateral two-dimensional terahertz images of obscured ring patterns are statistically validated with respect to their corresponding optical photographs via adapted dendrochronological methods. Results are compared to similar analysis of x-ray images of a wood specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 34 publications
(37 reference statements)
0
21
0
1
Order By: Relevance
“…only weakly absorbing the THz radiation as opposed to graphite. Further, TDS-THz has also been proposed for the study of tree rings in painted wood [160], the detection of delaminations [161] and for the detection of defects in a painted wooden panel [162].…”
Section: Terahertz Imagingmentioning
confidence: 99%
“…only weakly absorbing the THz radiation as opposed to graphite. Further, TDS-THz has also been proposed for the study of tree rings in painted wood [160], the detection of delaminations [161] and for the detection of defects in a painted wooden panel [162].…”
Section: Terahertz Imagingmentioning
confidence: 99%
“…[72] It has also been suggested that THz can be used to detect water content or damage in artifacts and artwork. [73] …”
Section: Paint and Art Preservationmentioning
confidence: 99%
“…This paper introduces THz technology and discusses its applications for Art and Archaeology. Its first test in this field dates back to 1998 when THz was investigated as a tool for dating wooden objects (dendrochronology) [39][40][41]. The same instrumental advancements that led the growing interest into this technology also generated research into a number of cultural heritage applications [42].…”
Section: Introductionmentioning
confidence: 99%